2015
DOI: 10.1177/1359105315577302
|View full text |Cite
|
Sign up to set email alerts
|

Association of biological, psychological and lifestyle risk factors for eating disturbances in adolescents

Abstract: We aimed to assess the association of several risk factors for eating disturbances in adolescents. Participants were 448 girls and boys aged 12-15 years. Being female, higher body mass index, internalisation of standard of appearance, perfectionism, body dissatisfaction, number of lifetime addictive behaviours and lower self-esteem were associated with higher eating disturbance scores, whereas frequency of sedentary behaviours and physical activity were not (R(2) ⩾ 41%). Findings suggest the need to guide prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 53 publications
2
18
0
7
Order By: Relevance
“…This study shows that girls of mean age of 13 years have more symptoms of ED than boys of the same age, as documented in previous literature in different age groups (Gutiérrez et al, 2015; Micali et al, 2017; Pisetsky, Chao, Dierker, May, & Striegel‐Moore, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…This study shows that girls of mean age of 13 years have more symptoms of ED than boys of the same age, as documented in previous literature in different age groups (Gutiérrez et al, 2015; Micali et al, 2017; Pisetsky, Chao, Dierker, May, & Striegel‐Moore, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were observed by Francisco et al (2015) who showed a significant positive correlation between EDI‐P and EAT‐26. Gutiérrez et al (2015) confirmed this association after assessing the simultaneous influence of perfectionism and other personality risk factors (i.e., impulsiveness) on EAT‐26 overall score.…”
Section: Narrative Synthesismentioning
confidence: 87%
“…Such results are not replicable in girls from our findings. It is not sure if the function of physical activity was compromised by other health behavioral problems, such as eating disturbance in girls, resulting in a net increase in BMI and poorer body esteem [13]. Different results are reported in Western countries.…”
Section: Discussionmentioning
confidence: 98%